Prevalencia de trastornos osteomusculares y su repercusión en la salud en médicos cirujanos de la sociedad de cirugía de Pichincha - Hernández Espinosa, Ruth Alba (2023)
The study developed focused on the problem of musculoskeletal disorders, which impact the health of surgeons who are members of the Pichincha Surgery Society. Musculoskeletal disorders constitute a series of alterations that affect each of the structures that make up the musculoskeletal system and specifically the musculoskeletal system. Therefore, the objective corresponds to; determine the prevalence of musculoskeletal disorders and their impact on health in surgeons of the Pichincha Surgery Society. The research was carried out using a quantitative, transversal approach, with a deductive and experimental methodology, taking into consideration a population of 250 and a sample of 50 surgeons from the Pichincha Surgery Society, to whom the Standardized Nordic Questionnaire was applied as an instrument. Among the main results obtained, they say that, during the last seven days, 24% have had pain, discomfort or discomfort at the neck level, while 28% had shoulder problems. On the other hand, 32% had elbow problems and 12% had wrist problems. In another context, 38% presented these problems in the lumbar area, 22% in the lumbar area, 20% in one or both hips and finally, 26% in one or both ankles. It is concluded that the prevalence of musculoskeletal disorders in the members of the Pichincha Surgery Society corresponds to 22%.